2022
DOI: 10.1111/aji.13591
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR+ CD45RAˉ Tregs and CD28ˉ Treg‐like cells: Potential immunologic biomarkers for reproductive aging

Abstract: Problem This study aimed to identify subsets of regulatory T cells (Tregs) associated with ovarian aging and determine whether they can be used as markers of reproductive aging. Method This prospective cohort study was conducted among women of reproductive age. Basic physiological characteristics, reproductive hormones, Treg cell subsets, and correlations between these parameters were assessed. The POSEIDON criteria was used to identify women with low reproductive potential. Results The percentages of HLA‐DR+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The level of DR + memory Tregs shows a significant positive correlation with the level of blood follicle-stimulating hormone (FSH) and a significant negative correlation with the level of anti-müllerian hormone (AMH) and antral follicle count (AFC). Furthermore, the level of CD28 -Tregs is negatively correlated with the level of AFC (122). Thus, as indicated by the above-described results, Tregs subpopulations are associated with ovarian reserve markers, and the composition of Tregs pool subpopulations is expected to be useful in assessing ovarian function and predicting subsequent reproductive potential.…”
Section: Memory Tregs and Reproductive Potentialmentioning
confidence: 67%
“…The level of DR + memory Tregs shows a significant positive correlation with the level of blood follicle-stimulating hormone (FSH) and a significant negative correlation with the level of anti-müllerian hormone (AMH) and antral follicle count (AFC). Furthermore, the level of CD28 -Tregs is negatively correlated with the level of AFC (122). Thus, as indicated by the above-described results, Tregs subpopulations are associated with ovarian reserve markers, and the composition of Tregs pool subpopulations is expected to be useful in assessing ovarian function and predicting subsequent reproductive potential.…”
Section: Memory Tregs and Reproductive Potentialmentioning
confidence: 67%
“…Similarly, Desdín-Micó et al (Desdín-Micó et al, 2020) reported that CD4 + T cells with dysfunctional mitochondria due to mitochondrial transcription factor A (TFAM) deficiency produced high levels of inflammatory cytokines IL-6, TNFα, etc., which act as accelerators of senescence. Muyayalo et al (Muyayalo et al, 2023) suggested that the percentages of HLA-DR CD45RA-Tregs and CD28-Treg-like cells significantly increased with age and can serve as immunologic markers of reproductive aging. Additionally, Li et al (Li et al, 2022) revealed that aging altered immune cell responses, especially by toning down Th17 cells, counteracting experimental autoimmune uveitis challenge in old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Muyayalo et al. (Muyayalo et al., 2023 ) suggested that the percentages of HLA‐DR CD45RA‐Tregs and CD28‐Treg‐like cells significantly increased with age and can serve as immunologic markers of reproductive aging. Additionally, Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to classify patients from an autoimmune perspective and provide graded treatment, with the aim of improving clinical outcomes 4–6 . Researchers have also employed a multi‐omics approach to identify biomarkers of pregnancy loss and predict reproductive aging, enabling clinicians to establish personalized therapeutic strategies 7–9 . Although researchers have found ways to manage and intervene clinically from an immune perspective in patients with clear immune alterations, the complexity of the national context and patient profile results in clinical design being subject to confounding factors and selection bias, leading to a relatively low level of evidence.…”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
“…[4][5][6] Researchers have also employed a multi-omics approach to identify biomarkers of pregnancy loss and predict reproduc-tive aging, enabling clinicians to establish personalized therapeutic strategies. [7][8][9] Although researchers have found ways to manage and intervene clinically from an immune perspective in patients with clear immune alterations, the complexity of the national context and patient profile results in clinical design being subject to confounding factors and selection bias, leading to a relatively low level of evidence. For instance, intrauterine injection of hCG has been suggested to increase endometrial Tregs in patients with Treg-reduced repeat implantation failure (RIF) with concomitant improvement in pregnancy outcome.…”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%